In vitro Antioxidant Activity of Leaves of Ficus rumphii Blume - Pal, D.K.; Maity, P.; Samanta, K. (Asian Journal of Chemistry, 2010)
The in vitro antioxidant activity of aerial parts of Ficus rumphii Blume has been investigated by estimating degree of non-enzymatic haemoglobin glycosylation measured colorimetrically at 520 nm. The chloroform and aqueous extract of aerial parts of F. rumphii showed higher antioxidant activity than other extracts of it. The antioxidant activity of the extracts is close and comparable to that of standard antioxidant compounds used.